METABOLIC STATE OF BLOOD LYMPHOCYTES IN CHRONIC MYELOID LEUKEMIA AND CHRONIC LYMPHOID LEUKEMIA - O. V. Smirnova; V. T. Manchuk; A. A. Savchenko (Медицинская иммунология)
Abstract. We examined metabolic status of blood lymphocytes in forty-four patients with chronic myeloid leukemia (CML), and in fifty-seven patients with chronic lymphoid leukemia (CLL). The most pronounced changes of enzyme activities are found in blood lymphocytes of CML and CLL patients during terminal stage of the disease. All the patients with chronic leukemia at both stages showed a decreased intensity of metabolic processes in blood lymphocytes. In addition, CML patients at both clinical stages exhibited a decrease in antioxidant cell protection. The more pronounced biochemical disturbances in CML patients at progression stage concerned carbohydrate metabolism, whereas the changes at terminal stage of disease affected both carbohydrate and fat metabolism. The most marked biochemical alterations in CLL at progression stage are registered for carbohydrate and protein metabolism, and carbohydrate, fat and protein metabolism at terminal stage of disease. The revealed changes showed indicate to more severe clinical course in the patients with CML. These changes and differences depict some aspects of immune pathogenesis in development and progression of CML and CLL.